2003
DOI: 10.1016/s0168-6445(03)00054-8
|View full text |Cite
|
Sign up to set email alerts
|

The SmtB/ArsR family of metalloregulatory transcriptional repressors: structural insights into prokaryotic metal resistance

Abstract: The SmtB/ArsR family of prokaryotic metalloregulatory transcriptional repressors represses the expression of operons linked to stressinducing concentrations of di-and multivalent heavy metal ions. Derepression results from direct binding of metal ions by these homodimeric 'metal sensor' proteins. An evolutionary analysis, coupled with comparative structural and spectroscopic studies of six SmtB/ArsR family members, suggests a unifying 'theme and variations' model, in which individual members have evolved disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
467
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(499 citation statements)
references
References 61 publications
(206 reference statements)
13
467
0
6
Order By: Relevance
“…Fura-2 was selected for initial experiments because its affinities for Mn 2+ , Fe 2+ , Co 2+ , and Cd 2+ ions are known and are in a range (picomolar to nanomolar) observed for many metalloregulatory proteins (40). Surprisingly, in our competition experiments between Fura-2 and MntR, where MntR was present in a 10-fold excess over Fura-2, MntR proved unable to compete for the metal ions Mn 2+ , Co 2+ , and Cd 2+ .…”
Section: Fluorescence Anisotropy Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fura-2 was selected for initial experiments because its affinities for Mn 2+ , Fe 2+ , Co 2+ , and Cd 2+ ions are known and are in a range (picomolar to nanomolar) observed for many metalloregulatory proteins (40). Surprisingly, in our competition experiments between Fura-2 and MntR, where MntR was present in a 10-fold excess over Fura-2, MntR proved unable to compete for the metal ions Mn 2+ , Co 2+ , and Cd 2+ .…”
Section: Fluorescence Anisotropy Experimentsmentioning
confidence: 99%
“…Both dyes are frequently employed as ratiometric Ca 2+ /Mg 2+ chelators but can also bind transition metal ions with related spectral changes. The affinities of Fura-2 for several transition metal ions has been determined (20,32-34), while for Mag-fura-2 only the binding constant with Zn 2+ has been reported (35).Fura-2 was selected for initial experiments because its affinities for Mn 2+ , Fe 2+ , Co 2+ , and Cd 2+ ions are known and are in a range (picomolar to nanomolar) observed for many metalloregulatory proteins (40). Surprisingly, in our competition experiments between Fura-2 and MntR, where MntR was present in a 10-fold excess over Fura-2, MntR proved unable to compete for the metal ions Mn 2+ , Co 2+ , and Cd 2+ .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Members of this family typically function as transcriptional repressors, responding to divalent and multivalent heavy metal ions and controlling the expression of genes involved in metal uptake, efflux, sequestration, or detoxification [40]. In the presence of heavy metal ions, their DNA binding activity are inhibited, allowing derepression of target genes [40].…”
Section: Discussionmentioning
confidence: 99%
“…Although the functions in these organisms are still unknown, a Pfam 2 database search revealed that PH1061 has a helix-turnhelix (HTH) motif ("HTH_5 motif" in the Pfam database), which may suggest that it is a DNA-binding protein like members of the ArsR family. 3 ArsR is a transcriptional repressor of the arsenic resistance operon in Escherichia coli, and other members of this family involve zinc-sensing transcriptional repressors, such as CzrA 4 from Staphylococcus aureus and SmtB 5 from Synechococcus pcc7942. The primary sequence similarities to PH1061 are 20%, 21%, and 6.6% with ArsR, CzrA, and SmtB, respectively.…”
mentioning
confidence: 99%